Observations on the effect of transthoracic echocardiography on hemodynamics, inflammatory stress response and pain mediators in patients with severe aortic stenosis - Deng, Fanxin; Chen, Aidong; Chen, Bin; Yang, Bo; Shi, Xiaoming; Xu, Zhipeng (Journal of Medical Biochemistry, 2025)
Background: Transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) are two of the most commonly used echocardiographic protocols in clinical practice. In this study, we compared the differences in the effects of the two echocardiographic protocols on hemodynamics, inflammatory stress response, and pain mediators in patients with severe aortic stenosis (AS).Methods: 204 patients with severe AS who were treated with Transcatheter aortic valve replacement (TAVR) in our hospital from January 2022 to February 2024 were selected as the research subjects. Among them, 109 patients received TTE (TTE group), and another 95 patients received TEE (TEE group). Differences in the evaluation effects of preoperative echocardiography and multislice helical computed tomography (MSCT) in all patients were compared, and changes in echocardiographic parameters before and after surgery were observed. In addition, the differences in postoperative hemodynamics, cardiac function[Brain natriuretic peptide (BNP), cardiac troponin I (cTnI), Creatine kinase isoenzyme (CK-MB)], stress response [Superoxide dismutase (SOD), Malondialdehyde (MDA)], inflammatory factors [Interleukin-1β/6 (IL-1β/6), Tumor necrosis factor-α (TNF-α)], and pain mediators [5-hydroxytryptamine (5-HT), Endothelin-1 (ET-1), Prostaglandin E2 (PGE2), Substance P (SP)] between the observation and TTE groups were compared.Results: No differences were identified in the evaluation of the aortic root between echocardiography and MSCT (P>0.05). After surgery, parameters such as LVESD and IVST decreased, while LVEF and AVA increased (P
Keywords: Transesophageal echocardiography; Aortic stenosis; Transthoracic echocardiography; Inflammatory factors; Stress response